Pengaruh Kebijakan Deviden, Profitabilitas Dan Struktur Kepemilikan Institusional Terhadap Struktur Modal Dan Nilai Perusahaan - waldelmi, idel (Jurnal Daya Saing, 2016)
Abstract: The present research was set to investigate the effect of dividend policy, profitability dan institutional ownership structure to the capital structure and company value of manufacturing companies listed at Indonesia Stock Exchange. The sample consisted of 78 manufacturing companies which were selected using a purposive sampling technique. The data source came from Indonesia Stock Exchange and ICMD (2010 – 2012) dan emittent financial data. The data were analyzed with path analysis which was applied withSPSS software, the hypotheses were tested using a t-test. The results show that (1) The significance test results of ANOVA table indicated significance value for 0.645, where 0.645 > 0.05. Thus, Ho was accepted and Ha was rejected. It means that the coefficient of regression was not significant. The conclusion was that variables X1, X2 and X3 had no effect or contribution to variable Y. (2) The significance test results of ANOVA table indicated the significance value for 0.000, where 0.000 <0.05. Thus, Ho was rejected and Ha was accepted. It means that the coefficient of regression was significant. Thus, the conclusion was that variables Y1, X1, X2 and X3 had effects or contributions to variable Y2. Keywords: dividend policies, profitability, institutional ownership structure, capital structure and company value